2003
DOI: 10.1197/jamia.m1377
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pediatric Respiratory and Diarrheal Outbreaks from Sales of Over-the-counter Electrolyte Products

Abstract: Sales of electrolyte products contain a signal of outbreaks of respiratory and diarrheal diseases in children and usually are an earlier signal than hospital diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 16 publications
2
55
0
Order By: Relevance
“…Our findings confirm previous studies that demonstrate the utility of using drug sales, and the timing of drug sales, compared to other indicators ( 8 , 15 ), as a proxy indicator of ILI activity. Several arguments support the need to consider syndromic surveillance based on drug-sales data.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirm previous studies that demonstrate the utility of using drug sales, and the timing of drug sales, compared to other indicators ( 8 , 15 ), as a proxy indicator of ILI activity. Several arguments support the need to consider syndromic surveillance based on drug-sales data.…”
Section: Discussionsupporting
confidence: 90%
“…However, we would argue that attendees at the paediatric outpatients' clinic are a reasonable control group in this context. Hospital attendances with diarrhoea are strongly temporally correlated with community diarrhoeal illness rates (Hogan et al 2003). As such our study does suggest that the use of the LifeStrawY can lead to a reduction in diarrhoeal disease, as least in the short term.…”
Section: Ministry Of Health Central Bureau Of Statistics and United supporting
confidence: 55%
“…Investigators have suggested several supplemental approaches for influenza surveillance, at prediagnosis and diagnosis stages. Prediagnosis approaches mainly include the analysis of information collected before specific influenza-related diagnoses are made, including analyses of telephone triage calls [16], purchases of over-the-counter medications for respiratory diseases [17][18][19][20], and school absenteeism [21]. In contrast, diagnosis-level approaches attempt to gather clinical data from emergency department visits [22][23][24] or microbiologic sources in as close to real-time as possible.…”
Section: Discussionmentioning
confidence: 99%